Management, interventions and stakeholders in the recovery of the Historic Center of Rimac - Palpán López, Saly (2023)
In the interest of pointing towards the comprehensive intervention of historical centers, the issue of management is posed as a system that articulates all actions on historical centers in their different tangible and intangible dimensions. In this way, management as an object of study allows an approach to the dynamics of multidimensional rehabilitation, in relation to the emerging themes of urban study, multiscalar, in the articulation of the different scales of planning and government; and multiactoral, in the implication in the decision making of diverse subjects and their interests on the territory. The objective of the article is to contribute to the knowledge about the area corresponding to Rimac´s district in the Historic Center of Lima, which in recent years has been recognized locally and internationally as the Historic Center of Rimac. From a historical perspective, it´s proposed the recognition of the management system in the recovery of the Historic Center of Rimac generated by stakeholders involved in the period 1991-2018. Likewise, heritage values ​​and discourses were identified from the thematization of management processes and the participation of specific social actors in those processes.